The duality of presence and absence in Tashari's by Enaam Kajaji - Safa Jamal Dawood (Zanco Journal of Humanity Sciences)
The research deals with the issue of presence and absence in Tashari’s novel by the Iraqi writer Ana’am Kaja Ji, and after presenting a glimpse into the concept of presence and absence, linguistically and idiomatically, and providing a glimpse into the novelist and her novel. the research aims to trace the effect of the duality of presence and absence in the narrative construction of the novel at the level of personality, Dialogue, time, and lastly at the level of place in the linguistic fabric of the novel (Tashari).